A Social Gospel Experiment: C. S. Eby’s People’s Institute in Early 20th-Century Toronto - McIntyre, Heather (Labour / Le Travail, 2025)
In 1909, an atypical church emerged in Toronto’s industrial core, the “People’s Institute,” which closed its doors less than two years later. Helmed by missionary C. S. Eby, the People’s Institute was an experiment designed to encourage political involvement and spread a Christian anti-capitalist ethic. This article situates the People’s Institute in the changing landscape of 1909 Toronto and within the larger trends of the labour church and the social gospel. It also argues that Eby’s experiment serves as an example of broader obstacles that prevented the long-term flourishing of left-wing approaches to Christianity in Canada.